Self-Assembly Formation of Lipid Bilayer Coatings on Bare Aluminum Oxide: Overcoming the Force of Interfacial Water - Jackman, Joshua Alexander (2016)
Widely used in catalysis and biosensing applications, aluminum oxide has become popular for surface functionalization with biological macromolecules, including lipid bilayer coatings. However, it is difficult to form supported lipid bilayers on aluminum oxide, and current methods require covalent surface modification, which masks the interfacial properties of aluminum oxide, and/or complex fabrication techniques with specific conditions. Herein, we addressed this issue by identifying simple and robust strategies to form fluidic lipid bilayers on aluminum oxide. The fabrication of a single lipid bilayer coating was achieved by two methods, vesicle fusion under acidic conditions and solvent-assisted lipid bilayer (SALB) formation under near-physiological pH conditions. Importantly, quartz crystal microbalance with dissipation (QCM-D) monitoring measurements determined that the hydration layer of a supported lipid bilayer on aluminum oxide is appreciably thicker than that of a bilayer on silicon oxide. Fluorescence recovery after photobleaching (FRAP) analysis indicated that the diffusion coefficient of lateral lipid mobility was up to 3-fold greater on silicon oxide than on aluminum oxide. In spite of this hydrodynamic coupling, the diffusion coefficient on aluminum oxide, but not silicon oxide, was sensitive to the ionic strength condition. Extended-DLVO model calculations estimated the thermodynamics of lipid–substrate interactions on aluminum oxide and silicon oxide, and predict that the range of the repulsive hydration force is greater on aluminum oxide, which in turn leads to an increased equilibrium separation distance. Hence, while a strong hydration force likely contributes to the difficulty of bilayer fabrication on aluminum oxide, it also confers advantages by stabilizing lipid bilayers with thicker hydration layers due to confined interfacial water. Such knowledge provides the basis for improved surface functionalization strategies on aluminum oxide, underscoring the practical importance of surface hydration.